Analysis of fresh air temperatures for air conditioning system in a hotel - Barańska, patrycja; Zając, Agnieszka (Instal, 2020)
This article presents the analysis of outdoor air temperatures in air conditioning system based on fan coils. The project has been realized for a hotel. This analysis shows how differents tempertaures of outside air affect the operating system, annual energy consumption and operating costs.